Relative importance of performance factors in winning NBA games in regular season versus playoffs - Teramoto, M.; Cross, Ch. L. (Journal of Quantitative Analysis in Sports, 2010)
In the National Basketball Association (NBA), there are high expectations for the post-season among the teams having the league's best regular season records. However, not every team who plays great basketball in the regular season will succeed in the playoffs. The Phoenix Suns, for example, had the third best regular season record from the 2004-05 through 2006-07 seasons; however, not once did they reach the NBA Finals during those years. We hypothesized that how teams win games in the NBA differs between the regular season and the playoffs. This paper discusses the relative importance of performance factors in winning basketball games in the past 10 years of the NBA (between the 1999-2000 and 2008-2009 seasons). Specifically, we examined the contributions of overall efficiency (offensive and defensive ratings), along with the Four Factors (effective field goal percentage, turnover percentage, rebound percentage, and free throw rate) to winning games in the regular season and the playoffs, using a multiple linear regression and a logistic regression analysis. The results of these analyses indicate that efficient offense and defense are both essential to be successful in the regular season and the playoffs, but the importance of defense in winning games may be greater in the playoffs than in the regular season. Shooting efficiency on both ends of the floor (offensive and defensive effective field goal percentages) seems to be the most critical aspect of the game in the regular season as well as the playoffs. In addition, committing fewer turnovers could be another key to winning games, especially in the regular season. It appears that defense becomes more important for winning playoff series as a team advances further in the post-season. Lastly, rebounding may play a significant role in deciding the outcome of the Conference Finals where two teams most likely have similar shooting efficiency and turnover rates.